Dental Professionals' Knowledge Towards Minimal Intervention Dentistry Regarding Caries Management in the Public Health Service in Vitória da Conquista, Brazil - Taiomara Vieira Mania; Natalia Bertolo Domingues; Daniela Prócida Raggio (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the knowledge of dental professionals and attitudes regarding dental caries management according to minimal intervention dentistry (MID). Material and Methods: Sixty-four dentists working in the public health service of Vitória da Conquista, Brazil, were invited to answer an online questionnaire structured into four domains. Descriptive data analysis and the association between demographic aspects and knowledge about MID for caries management were performed by Fisher's exact test (α=5%). Results: Among the 53 respondents (82.8% response rate), 67.9% were women aged 31-40 years (39.6%), working in primary health care (75.5%) and general practice (64.2%). Although professionals claimed to know MID for caries management (81.1%), considering its performance in their clinical practice (58.5%), regular knowledge was verified (84.9%), which is associated with self-assessment of the benefit provided by the technique (p=0.013). Uncertainties regarding the use of fluoride to inactivate lesions and dental sealants for prevention and treatment were highlighted. Hesitancy in disagreeing with statements related to incorrect etiology and traditional caries management was also observed. The main barriers identified for MID use were insecurity and the unavailability of adequate instruments/materials in the service. Conclusion: Although professionals have demonstrated regular knowledge about the benefits of MID in managing dental caries lesions, there is a lack of knowledge and attitudes related to the technique and barriers to its use in clinical practice.